2015
DOI: 10.1111/iju.12999
|View full text |Cite
|
Sign up to set email alerts
|

Periodical measurement of urine volume in the bladder during sleep: Temporary volume reduction suggestive of absorption

Abstract: Objectives: To clarify the variance of urine volume in the urinary bladder during sleep. Methods: Overnight measurements of urinary bladder capacity during sleep were carried out using transabdominal real-time 3-D ultrasound or an automatic capacity recorder, Yuririn, in 24 volunteers of various ages. Results: Two types of patterns were observed in the increasing curve of capacity; namely, gradual elevation pattern when overnight urine production was less than functional bladder capacity and steep-flat pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Moreover, this study revealed that periodic measurements of bladder volume by the Lilium α‐200 were well correlated with instilled volume during V‐UDS. This is especially promising because few US bladder scanners can be fixed onto the suprapubic region, meaning it has been difficult to monitor bladder volume periodically with other existing US bladder scanners . Therefore, the results of this study suggest that periodic monitoring of bladder volume by the Lilium α‐200 could be feasible within the normal range of bladder volume when patients are in the supine position.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, this study revealed that periodic measurements of bladder volume by the Lilium α‐200 were well correlated with instilled volume during V‐UDS. This is especially promising because few US bladder scanners can be fixed onto the suprapubic region, meaning it has been difficult to monitor bladder volume periodically with other existing US bladder scanners . Therefore, the results of this study suggest that periodic monitoring of bladder volume by the Lilium α‐200 could be feasible within the normal range of bladder volume when patients are in the supine position.…”
Section: Discussionmentioning
confidence: 98%
“…Children with nocturnal enuresis do not wake up or elderly people with nocturia wake up when they feel the urge to urinate when the bladder reaches its functional capacity. However, in 2016, Watanabe and Azuma reported a new concept of bladder absorption to avoid nocturnal enuresis or nocturia. During the “steep‐flat pattern,” the bladder reaches its functional capacity shortly after sleep onset and is maintained steadily at the functional capacity until wake time in the morning.…”
Section: Introductionmentioning
confidence: 99%
“…During the “steep‐flat pattern,” the bladder reaches its functional capacity shortly after sleep onset and is maintained steadily at the functional capacity until wake time in the morning. In the process, a temporary reduction in bladder volume occurs, which is suggestive of water absorption from urine in the bladder . Animal experiments demonstrated that intravesical fluid is absorbed in some conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent studies are most common though larger animals are also used to model the human treatment situation more closely. Since human bladder capacity is approximately 500 ml,(62) the small size of bladder in mice (~ 0.15 ml) and rats (~ 1 – 1.5 ml) requires different heating systems(58, 63). Farm pigs are also used for preclinical studies, with bladder volumes ranging from 250 ml to larger than human bladders.…”
Section: Devices and Techniques For Pre-clinical Bladder Heatingmentioning
confidence: 99%